THE EFFECT OF FINGERPRINTS ON THE PERFORMANCE OF OFFICERS (Study of SME and Industrial Cooperatives in Bantul) - Jumiati Jumiati; Ulung Pribadi; Muhammad Rusli (DIA: Jurnal Administrasi Publik, 2020)
The fingerprint is digital access used on a person's fingerprint (thumb) in filling in the presence of a bio. The purpose of this study is to be able to know how far functional fingerprints are to the discipline of the employees in the Cooperative Office of SMEs Bantul Regency. Fingerprint itself is present to make it easier for humans to fill in attendance bio to streamline employees' time in office activities. Employees of SME cooperatives Bantul Regency is very helped by the fingerprint itself as one of the means that facilitates employees in continuing the activity of Their data used in this study is secondary data and literature study surveys by taking from several sources such as websites to obtain relevant results.